The social determinants of health associated with cardiometabolic diseases among Asian American subgroups: a systematic review - Lucy Y. Min; Rehnuma B. Islam; Nikhila Gandrakota; Megha K. Shah (BMC, 2022)
Abstract Background Asian Americans represent one of the fastest-growing immigrant groups in the U.S. and are at high risk for cardiometabolic diseases (CMDs), including type 2 diabetes, hypertension, coronary artery disease, and stroke. Despite the growth of Asians in the U. S, there is a gap in understanding the heterogeneity of CMDs across Asian subgroups and how these might be affected by the social determinants of health (SDOH), or the environment in which people live and work. Objective The purpose of this systematic review is to examine the current literature on CMDs among Asian Americans and identify the SDOH that are associated with the incidence and/or prevalence of CMDs among specific Asian subgroups. Methods PubMed, Embase, Web of Science were searched for articles published in Jan 2000-Nov 2020. The reproducible strategy yielded 2732 articles. The articles were reviewed based on the following inclusion criteria: (1) observational study published in the U.S., (2) adult population includes specific Asian subgroups, (3) exposures include SDOH, and (4) outcomes include a CMD, defined as type 2 diabetes, hypertension, coronary artery disease, or stroke. Results In this review, 14 studies were identified and organized into four key themes: acculturation (n = 9), socioeconomic status (SES) (n = 6), social context (n = 2), and health literacy (n = 1). The most represented Asian subgroups in the literature were Chinese, Filipino, and South Asians. Acculturation was the most described social factor in the included reviews. Seven studies found associations between higher acculturation levels and higher prevalence of CMD. However, the measure of acculturation varied by study and included various combinations of the country of birth, number of years residing in the U.S., and English proficiency. The effects of SES, measured as income level and educational attainment, varied by racial subgroups. One study found that higher levels of education were associated with CMD among South Asians. Conclusion Acculturation, SES, social context, and health literacy impact the risk of CMD among Asian Americans; these vary across subgroups. Future research disentangling SDOHs on the risk of CMDs by Asian subgroup is necessary to provide better informed preventive practices and interventions.